2014
DOI: 10.1002/jcb.24753
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Risks Associate With Genetic Polymorphisms of XRCC1 Gene in Chinese Population

Abstract: Glioma is the most common type of primary brain tumors in adults. Previous evidence indicates that the X-ray repair cross-complementing group 1 gene (XRCC1) is an important candidate gene which influencing the pathogenesis of glioma. This study aims to assess the potential associations between glioma risks and genetic polymorphisms of XRCC1 gene. A total of 1,286 Chinese Han ethnic subjects consisting of 638 glioma patients and 648 controls were recruited in this case-control study. The genotyping of XRCC1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that XRCC1 gene polymorphisms contribute to the development of cancers, such as lung, colorectal, breast, and ovarian cancers (Guo et al, 2015;Malisic et al, 2015;Nissar et al, 2015;Wang et al, 2015b). Recently, several epidemiologic studies have assessed the association between XRCC1 gene polymorphisms and susceptibility to glioma, but their findings are inconclusive (Feng et al, 2014;Li et al, 2014;Rodriguez-Hernandez et al, 2014;Wang et al, 2015a). In our study, we examined a Chinese Han population and investigated the role of XRCC1 gene polymorphisms (Arg399Gln and Arg194Trp) with a risk for susceptibility to gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that XRCC1 gene polymorphisms contribute to the development of cancers, such as lung, colorectal, breast, and ovarian cancers (Guo et al, 2015;Malisic et al, 2015;Nissar et al, 2015;Wang et al, 2015b). Recently, several epidemiologic studies have assessed the association between XRCC1 gene polymorphisms and susceptibility to glioma, but their findings are inconclusive (Feng et al, 2014;Li et al, 2014;Rodriguez-Hernandez et al, 2014;Wang et al, 2015a). In our study, we examined a Chinese Han population and investigated the role of XRCC1 gene polymorphisms (Arg399Gln and Arg194Trp) with a risk for susceptibility to gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Gliomas may be caused by both intrinsic and environmental factors. Recently, a vast number of studies have shown that genetic factors such as single nucleotide polymorphisms (SNPs) play an important role in modifying glioma susceptibility (Feng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over 300 single nucleotide polymorphisms (SNPs) have been identified in XRCC1 (http://www.ncbi.nlm.nih.gov/ projects/SNP), and previous studies have also reported that a number of SNPs in DNA repair genes may modify glioma risk [9][10][11][12][13][14]. The most extensively studied has been rs25487 in codon 399 of exon 10, a non-synonymous G/A polymorphism changing arginine to glutamine.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some case-control studies and meta-analysis were carried out [10,[12][13][14][15][16][17]. However, the cumulative results are still inconclusive due to different ethnicities, research samples, ages and subtypes of glioma.…”
Section: Introductionmentioning
confidence: 99%